2016
DOI: 10.1155/2016/5749857
|View full text |Cite
|
Sign up to set email alerts
|

Review of Herbal Traditional Chinese Medicine for the Treatment of Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is the most serious chronic complications of diabetes; 20–40% of diabetic patients develop into end stage renal disease (ESRD). However, exact pathogenesis of DN is not fully clear and we have great difficulties in curing DN; poor treatment of DN led to high chances of mortality worldwide. A lot of western medicines such as ACEI and ARB have been demonstrated to protect renal function of DN but are not enough to delay or retard the progression of DN; therefore, exploring exact and fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 100 publications
0
69
0
Order By: Relevance
“…Activation of interstitial fibroblasts together with EMT can result in abnormal ECM accumulation, a hallmark of interstitial fibrosis, and eventually DN (Adeshara et al, ; Jha et al, ; Reddy et al, ; Scully, ; Sun et al, ). In this study, we showed in rat and NRK‐52E cell models that activation of the TGF‐β pathway is critical to DN pathogenesis by promoting EMT and excessive ECM deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of interstitial fibroblasts together with EMT can result in abnormal ECM accumulation, a hallmark of interstitial fibrosis, and eventually DN (Adeshara et al, ; Jha et al, ; Reddy et al, ; Scully, ; Sun et al, ). In this study, we showed in rat and NRK‐52E cell models that activation of the TGF‐β pathway is critical to DN pathogenesis by promoting EMT and excessive ECM deposition.…”
Section: Discussionmentioning
confidence: 99%
“…DN is still one of the main causes of chronic renal failure,37 and its treatment is far more complicated than that of general kidney disease, with a poor prognosis. Currently, western medicine mainly works to regulate the blood glucose, blood lipids, and blood pressure and to improve the microcirculation to control the disease; however, due to the lack of effective drug treatment, it is difficult to prevent the development of the disease 38. The etiology of DN is complex, and its pathogenesis, which involves many factors, is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In China, numerous CHMs are prescribed for DKD . The efficacies of classic Chinese prescriptions, such as Bawei Dihuang pill (八味地黄丸), Guizhi Fuling pill (桂枝茯苓丸), Liuwei Dihuang pill (六味地黄丸) and Wenpi decoction (温脾汤), have been validated by clinical trials .…”
Section: Treating Diabetic Kidney Disease With Chinese Medicinementioning
confidence: 99%